Observations on Some Arctic Soils of Southwest Devon Island, N. W. T., Canada - Jackson, Ronald Hugh (My University, 1970)
No abstract provided.
Scope and contents: An investigation into some arctic soils located on Southwest Devon Island. Some aspects of chemical weathering in the area are considered and detailed studies of patterned ground are undertaken. A terrain map was compiled to locate the major areas of soils and mineral and organic covers and to show this relationship to relief units.
Keywords: Arctic soils; Southwest Devon Island; North West Territories; chemical weathering; terrain map; relief unit